Yeast studies on ageing - Jazwinski, S. Michal (Henry Stewart Talks, 2016)
History of studies on yeast ageing, Senescence factor, molecular memory, and age locus, Mitochondria and ageing, Age asymmetry and cell quality control, Epigenetic gene regulation and ageing, Genome instability as a cause of ageing, Replicative and chronological lifespans, Nutrient effects on lifespan, Aging in the wild